2021
DOI: 10.1017/s0033291721001173
|View full text |Cite
|
Sign up to set email alerts
|

Misunderstanding precision psychiatry

Abstract: We thank van Os and Kohne for their reply to our commentary. It is true, we are in love with the concept of precision psychiatry. But we are not blindly in love. Our love for precision psychiatry is based on remarkable and rapid advances in biological psychiatryclosely linked to advances in technologythat support the potential of this paradigm shift. Some of these advances were presented in our previous commentary (Salagre & Vieta, 2021). Yet, van Os and Kohne question the foundations of precision psychiatry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There is an ongoing discussion about the need for precision medicine in mental health treatments, e.g., [31][32][33][34][35] and in mHealth [36][37][38] and possibly more newly developed apps will follow this promising path and pivot to the precision medicine research, first on undiagnosed individuals with needs in certain areas, and then on clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing discussion about the need for precision medicine in mental health treatments, e.g., [31][32][33][34][35] and in mHealth [36][37][38] and possibly more newly developed apps will follow this promising path and pivot to the precision medicine research, first on undiagnosed individuals with needs in certain areas, and then on clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…In this complex interrelation between the neuroendocrine and the immune–inflammatory processes, the presence of a transdiagnostic convergence across somatic and mental disorders of impaired inflammatory activity reinforces the significance of the scientific knowledge regarding comorbidity ( 79 , 80 ) as an essential field of research with a holistic perspective. The studies investigating comorbidity and its overlapping pathways have already shown that these associations provide an invaluable chance to broaden the horizons of what is currently known about the pathogenesis, progress, and repercussions of these pathologies, and may allow further progress in the context of “precision psychiatry” paradigm ( 81 ).…”
Section: Discussionmentioning
confidence: 99%